2016
DOI: 10.1007/s11033-016-3942-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery with nano-quercetin enhances doxorubicin-mediated cytotoxicity against MCF-7 cells

Abstract: Quercetin, the plant-derived phenolic compounds, plays a pivotal role in controlling hemostasis, by having potent antioxidant and free-radical scavenging properties. This flavonoid in combination with chemotherapeutic drugs improves the efficacy of these agents in induction of apoptosis in cancer cells. This study investigated the role of nano-quercetin (phytosome) in doxorubicin-induced apoptosis. Nanoparticles were characterized for particle size, zeta potential, scanning electron microscopy (SEM) and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(51 citation statements)
references
References 39 publications
4
44
0
Order By: Relevance
“…Quercetin enhanced the antitumor effect of doxorubicin in HT29 colorectal cancer cell line [19], MCF-7 breast cancer cell line [20], liver cancer cells [21], and K562 human leukemia cell line [22]. Quercetin also showed cardioprotection against cardiotoxicity induced by doxorubicin [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin enhanced the antitumor effect of doxorubicin in HT29 colorectal cancer cell line [19], MCF-7 breast cancer cell line [20], liver cancer cells [21], and K562 human leukemia cell line [22]. Quercetin also showed cardioprotection against cardiotoxicity induced by doxorubicin [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…NQO1 and HO-1 are two major downstream targets of Nrf2, and serve a pivotal role in the maintenance of cellular redox homeostasis, thus preventing the transformation of normal cells to precancerous or malignant ones by counteracting ROS-mediated carcinogenesis (40). However, it was demonstrated that NQO1, in parallel with Nrf2 overexpression, aberrantly elevated the levels of HO1 in different types of cancer (40,41). Minaei et al demonstrated the effectiveness of nano-Qin decreasing the levels of NQO1 and multidrug resistance-associated protein 1without altering Nrf2 expression (41).…”
Section: Discussionmentioning
confidence: 99%
“…Then, cells were replaced with 200 ll fresh media containing 20 ll of MTT solution (2 mg/ml) and incubated for 4 h at 37 C. Then, media was removed and 200 ll of DMSO and 25 ml of Sorenson-glycine buffer were added to dissolve the Formazon crystals. Finally, the absorbance at 570 nm after shaking for 15 min was measured using a microplate reader (Biotek, Winooski, VT) (Sharifi et al, 2015;Minaei et al, 2016).…”
Section: Cell Culture and Mtt Assaymentioning
confidence: 99%